PENTINGNYA PENGENDALIAN STRES KERJA DAN OPTIMALISASI KOMUNIKASI DALAM PENINGKATAN PRODUKTIVITAS KERJA - Anjaningrum, Widiya Dewi; Andarwatiningtyas, Ken (Creative Research Management Journal, 2023)
UD Esbas Toys, located in Pandaan, is one of the doll manufacturers that has successfully gone through critical challenges during the Covid-19 pandemic. This success can be seen from the relatively stable work productivity of employees to date as a result of the implementation of proper HR management. The main objective of this research is to confirm the strong influence of work stress and communication on employee productivity. A total of 35 employees of UD Sebas Toys Pandaan have been selected as the saturated sample technique. Respondents' perceptions were collected using a questionnaire where each statement in the questionnaire was given a 5-point Likert scale to form quantitative data which was finally analyzed using PLS. The results of the study revealed that work stress has a positive effect on productivity, although not too strong. While the positive effect of communication on productivity proved significant. So, it is important for every employee to control stress so that it continues to have a positive impact on productivity and optimize positive communication. The limitation of this research is the number of respondents which is only 35 people, the results of the research may be different if employees in other branches are considered. In addition, the analysis process has not included the demographics of the respondents as a control variable in the model. However, the results of the research contribute to the development of HRM science in relation to increasing employee productivity in small-medium scale manufacturing companies through controlling employee work stress and effective communication.